Analyzing Student Reactions to Interactive Learning Materials and Critical Thinking Capabilities Using the Rasch Model - Candrawati, Emilia; Uliyandari, Mellyta; Prahani, Binar Kurnia (Universitas Muhammadiyah Sidoarjo, 2025)
By creating interactive learning materials for the biochemistry course, this project seeks to improve the critical thinking abilities of students enrolled in the Science Education Program at one of the Bengkulu universities. Employing a research and development (R&D) approach considering the DDD-E (Decide, Design, Develop, Evaluate) model, the media was designed for Android devices and focuses on carbohydrate metabolism content. The main features include Program and Course Learning Outcomes, instructional materials, usage guidelines, and a profile section. Validation results from content and media experts confirmed the media’s appropriateness for instructional use. Student responses, analyzed using the Rasch Model, indicated strong agreement regarding the media's usefulness. Moreover, the application of this interactive media significantly improved students' critical thinking skills, with an N-gain score of 53.67%. These findings suggest that the media is effective for use in biochemistry courses, although further research is needed to explore its application in other subject areas.